Inhibition of METTL14 overcomes CDK4/6 inhibitor resistance driven by METTL14-m6A-E2F1-axis in ERα-positive breast cancer - Chenlin Liu; Dong Fan; Jiahui Sun; Guodong Li; Ruoxin Du; Xiaoshuang Zuo; Kuo Zhang; Wangqian Zhang; Shuning Wang; Xiaojv Li; Mingrui Du; Donghui Wang; et al. (Journal of Nanobiotechnology)
Abstract CDK4/6i, the first-line drug for treating ERα-positive breast cancer, significantly improves clinical outcomes. However, CDK4/6i resistance often develops and remains a major hurdle, and the underlying mechanisms remain challenging to fully investigate. Here, we used Genome-wide CRISPR/Cas9 library screening combined with single-cell sequencing to screen for molecules mediating CDK4/6i resistance and identified METTL14 as a determinant of CDK4/6i sensitivity. Clinical samples and datasets were analyzed and in vitro and in vivo experiments were performed to confirm the critical function of METTL14 in CDK4/6i resistance. Mechanistically, METTL14 can induce an increase in E2F1 expression in breast cancer cells via an m6A IGF2BP2-dependent mechanism and thus promote CDK4/6i resistance. Furthermore, through a small molecule screen, a novel METTL14 inhibitor named WKYMVM, which can restore sensitivity to CDK4/6i in CDK4/6i-resistant breast cancer cells, was identified. Treatment with folate-conjugated liposomes targeting breast cancer cells that contained both a CDK4/6i and WKYMVM revealed the synergistic effect of METTL14 inhibition with CDK4/6i therapy in a CDK4/6i-resistant PDX model. Together, our findings reveal the mechanism of CDK4/6i resistance and provide a strategy for overcoming CDK4/6i resistance via METTL14 inhibition. Graphical Abstract